A CFD Study on Leading Edge Wing Surface Modification of a Low Aspect Ratio Flying Wing to Improve Lift Performance. Issue 3 (September 2015) - Ramprasadh, C.; Devanandh, V.
Low Aspect Ratio (LAR, aspect ratio < 2) wings exhibit highly nonlinear lift curves. Controlling such LAR Mini Aerial Vehicles (MAVs) at high Angle of Attacks (AOA) and in cross-wind conditions is difficult due to the nonlinear lift. Also, maneuvering these MAVs at high AOA is highly constrained by elevator throw. However, high AOA is a requisite for MAVs to enable slow flight in constrained spaces. Conventional aircraft use devices called vortex generators (or turbulators) that delay the separation of boundary layer by artificially inducing vortices. A similar phenomenon is observed in golf balls, where the surface dimples mimic the above effect. It is also observed that the local vortices aid in additional lift generation. This paper presents a Computational Fluid Dynamics (CFD) study on the effect of dimples over the aerodynamic performance of a LAR flying wing with aspect ratio 1.45 & SELIG4083 cross section. A Modified Inverse Zimmerman planform wing has been considered similar to the MAV (Black Kite) developed by the National Aerospace Laboratories Bangalore (NAL). The 3D model was generated in SolidWorks ™ and CFD analysis was performed in SolidWorksTM Flow Simulation. The baseline smooth surface wing was validated with the aerodynamic data of SELIG4083 airfoil from literature. Following it, several dimpled wing configurations on the leading edge were created and analyzed. It was observed that dimples create local vortices that aid in lift generation, increasing the effective flight envelope. The associated drag due to local vortices should be overcome by generating additional thrust at high AOA.